Local tourism product development and promotion in the digital era - I Made Luhur Adi Putra; Dewa Gde Yoga Permana; Gita Apsari Dewi; A.A Gde Agung Nanda Perwira; Komang Tri Werthi (Universitas Pendidikan Indonesia, 2025)
This community service activity was conducted at SMA PGRI 2 Denpasar in response to the limited practice of students in developing and promoting local products, despite the material having been taught in theory in the curriculum. The primary objective of this activity is to enhance students' understanding and skills in developing local tourism products based on culture, as well as utilizing digital media as a promotional tool that is responsive to market needs. This service began with program socialization, local product development training (regional perfumes), and digital marketing training, including social media and content strategies. The methods employed included a total of 60 participants, participatory observation, interviews, questionnaires, documentation, and a SWOT analysis to evaluate the school's strategic position. The results of the activity showed a increase in student understanding after the training, as well as positive changes in interest, school community participation, and student readiness to market local products digitally. These findings emphasize the importance of cross-sector collaboration and an educational-participatory approach in developing sustainable and competitive local tourism products in the digital era. Abstrak Kegiatan pengabdian kepada masyarakat ini dilaksanakan di SMA PGRI 2 Denpasar sebagai respons atas terbatasnya praktik siswa dalam pengembangan dan promosi produk lokal, meskipun materi tersebut telah diajarkan secara teori dalam kurikulum. Tujuan utama kegiatan ini adalah untuk meningkatkan pemahaman dan keterampilan siswa dalam mengembangkan produk pariwisata lokal berbasis budaya, serta memanfaatkan media digital sebagai sarana promosi yang adaptif terhadap kebutuhan pasar. Pengabdian ini diawali dengan sosialisasi program, pelatihan pengembangan produk lokal (parfum khas daerah), serta pelatihan pemasaran digital menggunakan media sosial dan strategi konten. Metode yang digunakan meliputi total sampling terhadap 60 partisipan, observasi partisipatif, wawancara, kuesioner, dan dokumentasi, serta analisis SWOT untuk mengevaluasi posisi strategis sekolah. Hasil kegiatan menunjukkan adanya peningkatan pemahaman siswa setelah pelatihan, serta perubahan positif dalam minat, partisipasi komunitas sekolah, dan kesiapan siswa memasarkan produk lokal secara digital. Temuan ini menegaskan pentingnya kolaborasi lintas sektor dan pendekatan edukatif-partisipatif dalam pengembangan produk pariwisata lokal yang berkelanjutan dan kompetitif di era digital. Kata Kunci: pariwisata lokal; pengabdian masyarakat; pengembangan produk; promosi digital